2011
DOI: 10.2298/bah1103583g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymes supplementation on digestibility and energy utilizations of broilers diets with different metabolizable energy level

Abstract: In this 3х2 factorial design trial with three different levels of metabolizable energy (13.4, 13.00, 12.6 MJ/kg), with and without exogenous enzymes (nutrition density was reduced by introducing sunflower meal in different percentage to diet (0, 8 и 16%)), the goal was to investigate the effects of exogenous enzymes Roxazyme G2G (cellulase (endo-1,4-(β-glucanase), βglucanase (endo-1,3(4)-β-glucanase) and xylanase (endo-1,4-β xylanase)) on digestibility and energy utilization. Effects of enzymes were most visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Such degradation showed to produce oligosaccharides and disaccharides [ 65 ] with potential prebiotic functionality, while dismantling the cell wall structure and decreasing viscosity ( Table 2 ). Supplementation of MultiGrain to diets with sunflower meal (SFM) resulted in better performance in broiler chickens [ 67 ]. In the study, digestibility of the hemicellulose fraction of diets with 8 and 16% SFM was markedly enhanced (37 vs 54% and 15 vs 45%, respectively) by supplementation of the multicomponent carbohydrase product from T .…”
Section: Discussionmentioning
confidence: 99%
“…Such degradation showed to produce oligosaccharides and disaccharides [ 65 ] with potential prebiotic functionality, while dismantling the cell wall structure and decreasing viscosity ( Table 2 ). Supplementation of MultiGrain to diets with sunflower meal (SFM) resulted in better performance in broiler chickens [ 67 ]. In the study, digestibility of the hemicellulose fraction of diets with 8 and 16% SFM was markedly enhanced (37 vs 54% and 15 vs 45%, respectively) by supplementation of the multicomponent carbohydrase product from T .…”
Section: Discussionmentioning
confidence: 99%
“…Adding NSP-ase enzyme in sunflower-corn-based diet in broiler chicks has been reported to improve weight gain, FCR and digestibility (Khan et al, 2006). Glamocic et al (2011) reported that supplementation of exogenous enzyme (Roxazyme) with different levels of ME and SFM in broiler chicks increased the digestibility of CP, NDF, hemicellulose and ash, but the effects were most evident in diets with the reduced level of ME. A commercial multienzyme product (Zympex 008 â ) is reported to contain a-galactosidase, b-glucanase, amylase, xylanase, b-mannanase, protease and cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of xylanase facilitates animal performance, improves absorption of feed components, and increases the efficiency of meat and egg production [ 7 , 8 ]. The addition of xylanases in wheat-based diets can lower intestinal viscosity via the partial hydrolysis of wheat NSPs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%